The Life of Yusuf Shukru Harpûtî And His Works - Saylan, İbrahim (Fırat University, 2020)
Yusuf Şükrü, was born in Harput, after finishing his education here, he comp-leted the rest of his education in Egypt and Istanbul. After working at Istanbul Vefa madrasah for a while, he was appointed as a mudarris to Mahmudiyye Madrasah in Medina and he stayed till the end of his life and died there. In our study, the life of Harputi, his scientific personality, his unique paraphra-ses are examined. Harputi has seven works that we could find out. Some of these works are handwritten and some are printed. His unique works; Rumûzü’t-Tevhîd in the field of doctrines, Silsile-i Safâ in the field of the history of lineage and prophetic biography, and Nasihat-name which contains a lot of advices for the society and executives. His paraphrase works are Şerhu Usûli’l-Hadîs which hand-les the method of hadith, Nâmûsü’l-Îkân in the field of logic, Hâşiye-i ‘İsâm in the field of kalam, and Menba‘i’s-Se‘âde which includes invocations, salat and bles-sings in our daily life. Being known his scientific personality, introducing him, the works and life of Harputi who is one of the last representatives of the Ottomans’ both cultural and madrasah tradition, has a great importance. Harputi who has the ability of mudarris, sufi and poesy, showing the securing uniformity in his works with these aspects is another aspect of this work. We can specify the results as follows that we inferred from this work which we aim to introduce the life, scientific personality and works of Harputi who came from Harput and carried out his duty of mudarris in different regions of Ottoman. Harputi wrote copyright and paraphrase works both in Arabic and Ottoman Turkish in different fields not remaining insensitive to the political and social problems during in his era with his scientific and mystic identity. He has a broad perspective in the fields such as logic, politic and the history of lineage besides basic Islamic sciences. Besides Harputi’s copyright works in the field of politic, kalam, and prophetic biography, his paraphrases about the method of hadith and logic are also considered as unique works. Harputi was interested in Sufizm in addition to being mudarris, and got the Caliph of the Şazili and Nakşıbendi sect. Besides being known as a good poet, he used his poems as a tool to express his ideas.

Yusuf Şükrü, Harput’ta doğup, tahsilinin bir kısmını burada, kalanı ise Mısır ve İstanbul’da tamamlamıştır. İstanbul Vefâ Medresesi’nde bir süre görev yaptıktan sonra Medine’deki Mahmûdiyye Medresesi müderrisliğine tayin edilen Harpûtî, ömrünün sonuna kadar burada yaşamıştır. Çalışmamızda Harpûtî’nin hayatı, ilmî kişiliği, özgün ve şerh çalışmaları ince-lenmektedir. Harpûtî’nin tespit edebildiğimiz yedi eseri vardır. Bu eserlerden bazı-ları yazma bazıları ise matbudur. Özgün çalışmaları; akâid konusunda Rumûzü’t-Tevhîd, nesep tarihi ve siyer alanında Silsile-i Safâ ve halka ve yöneticilere öğütler içeren Nasîhat-nâme adlı eserleridir. Şerh çalışmaları ise hadis metedolijisini ele alan Şerhu Usûli’l-Hadîs, mantık ilminde Nâmûsü’l-Îkân, kelam alanında Hâşiye-i ‘İsâm ve günlük hayatta okunan zikir, salavat ve duaları içeren Menba‘i’s-Se‘âde adlı eserleridir. Osmanlı’nın gerek kültürel gerekse medrese geleneğinin son temsilcilerinden olan Harpûtî’nin hayatı, ilmî kişiliği ve telifatının bilinmesi, tanıtılması önem arz etmektedir. Müderris, mutasavvıf ve şairlik yönlerini bir arada bulunduran Harpû-tî’nin bu yönleriyle eserlerinde nasıl birliktelik sağladığını göstermek işin bir başka önemli boyutudur. Harput’tan çıkıp Osmanlı’nın farklı bölgelerinde müderrislik görevini ifa eden Harpûtî’nin hayatı, ilmî kişiliği ve eserlerinin tanıtılmasını amaçladığımız bu çalış-mada edindiğimiz sonuçları şöyle sıralayabiliriz. Harpûtî, ilmî ve tasavvufî kimli-ğiyle yaşadığı çağda toplumsal ve siyasal sorunlara duyarsız kalmayarak çeşitli dallarda Arapça ve Osmanlı Türkçesiyle telif ve şerh eserler kaleme almıştır. O, temel İslâmî ilimlerin yanı sıra mantık, siyaset ve nesep tarihi gibi alanlarda da geniş bir perspektif sahibidir. Nitekim Harpûtî’nin siyaset, kelam, siyer alanındaki telif eserlerinin yanında; usûlü’l-hadis ve mantık ilmine dair şerhleri de müstakil birer eser hüviyetindedir. Harpûtî, müderrisliğinin yanı sıra tasavvufla ilgilenerek Nakşibendî ve Şazilî Tarikatı’nın halifeliğini yapmıştır. Ayrıca şair olarak da tanı-nan Harpûtî, görüşlerini anlatmada şiirlerini bir araç olarak kullanmıştır.
YUSUF ŞÜKRÜ HARPÛTÎ’NİN HAYATI VE ESERLERİ